WISP1 Predicts Clinical Prognosis and Is Associated With Tumor Purity, Immunocyte Infiltration, and Macrophage M2 Polarization in Pan-Cancer - Liao, Xia; Bu, Yang; Xu, Zihan; Jia, Fengan; Chang, Fan; Liang, Junrong; Jia, Qingan; Lv, Yi (Frontiers in Genetics, 2020)
Cancer is becoming the leading cause of death and a major public health problem. Although many advanced treatment strategies are currently in use, the general prognosis of cancer patients remains dismal due to the high frequency of recurrence, metastasis. The identification of effective biomarkers is important for predicting survival of cancer patients and improving treatment efficacy. In this study, we comprehensively analyzed WNT1-inducible-signaling pathway protein 1 (WISP1) expression and explored its correlation with prognosis in pan-cancer using tumor IMmune Estimation Resource (TIMER) and Gene Expression Profiling Interactive Analysis 2 (GEPIA2). We also examined correlations between WISP1 and immunocyte infiltration using TIMER. We identified genes co-expressed with WISP1 using the LinkedOmics database and analyzed associated gene ontology using Metascape. Finally, we constructed protein-protein interaction networks and examined correlations between genes co-expressed with WISP1 and immunocyte infiltration in pan-cancer. WISP1 level differed between human pan-cancer tissues and normal tissues, indicating its potential as a prognostic biomarker. WISP1 expression was correlated with tumor purity and immunocyte infiltration, especially monocyte-macrophage trafficking and M2 polarization. Genes co-expressed with WISP1 were mainly associated with extracellular matrix organization, with collagen members COL6A3, COL5A1, and COL8A1 being key genes correlated with macrophage infiltration and M2 polarization in pan-cancer. Conversely, in certain types of cancer with better prognoses, WISP1 was associated with low M2 macrophage infiltration. These results suggest that WISP1 affect clinical prognosis through associations with tumor purity, immune cell infiltration, and macrophage M2 polarization in pan-cancer, with collagen member proteins may serving as effector molecules of WISP1.